Preparation and characterization of polyaniline nanofiber colloids1. Issue 8 (28th November 2012) - Qiu, Wei; Ma, Li; Gan, Mengyu; Bai, Youqian; Fu, Dandan; Li, Zhitao; Chen, Feifei
Abstract Polyaniline (PANI) nanofibers were prepared via the reaction of aniline with ammonium persulfate carried out in ethylene glycol (EG) medium without water. These purified PANI nanofibers could be dispersed in water and other polar solvents, such as ethanol, EG, and N, N‐dimethylformamide, to form colloids. The morphology and structure of the PANI nanofibers were characterized and the effects of mechanical stirring on the morphology, structure, and electrical performance of PANI were investigated. The results indicated that the intermolecular H‐bonding interaction between molecules of PANI and alcohol is advantageous to the one‐dimensional growth of PANI, and a stirring reaction results in a lager size, a higher doping level, conductivity, degree of crystallinity, and oxidation than a nonstirring reaction. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers.